A Systematic Review of Modifications and Validation Methods for the Extension of the Keystroke-Level Model. (5th December 2018) - Al-Megren, Shiroq; Khabti, Joharah; Al-Khalifa, Hend S.
Abstract : The keystroke-level model (KLM) is the simplest model of the goals, operators, methods, and selection rules (GOMS) family. The KLM computes formative quantitative predictions of task execution time. This paper provides a systematic literature review of KLM extensions across various applications and setups. The objective of this review is to address research questions concerning the development and validation of extensions. A total of 54 KLM extensions have been exhaustively reviewed. The results show that the original keystroke and mental act operators were continuously preserved or adapted and that the drawing operator was used the least. Excluding the original operators, almost 45 operators were collated from the primary studies. Only half of the studies validated their model's efficiency through experiments. The results also identify several research gaps, such as the shortage of KLM extensions for post-GUI/WIMP interfaces. Based on the results obtained in this work, this review finally provides guidelines for researchers and practitioners.